PENINGKATAN PEMASARAN DIGITAL PADA UMKM USAHA FASHION DI PASAR BAMBU KUNING BANDAR LAMPUNG - Purnomo, Agus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Micro, small and medium enterprises (MSMEs) are productive and independent economic businesses run by individuals and groups. One of the MSMEs is a business in the fashion sector that runs its business in the Bambu Kuning Market in Bandar Lampung. People are increasingly aware of fashion and fashion lifestyles, so the demand for fashion products is increasing. This shows that MSMEs in the fashion sector are growing quite rapidly, but have not effectively marketed their products. This is due to not having the knowledge and skills in digital marketing. The purpose of this activity is to empower and provide digital marketing training to MSMEs in the fashion business sector. This activity was carried out through lectures, discussions and social media practices. The response of the participants was very good, so that after this service activity was carried out, MSMEs could increase their understanding and skills in marketing their products through digital marketing. Keywords: Digital Marketing, MSMEs, Fashion